Customized Genioplasty and Advantages of 3D Virtual Planning: An Updated Literature Review - Illarramendi, Imanol Zubiate; Cariati, Paolo; Martínez-Sahuquillo, Ángel; Iglesias, Fernando Monsalve (Facial Plastic Surgery, 2024)
Genioplasty is a surgical technique that modifies the projection of the chin in three dimensions to achieve symmetry and facial harmonization. Virtual 3D planning is increasingly used, supplanting the conventional surgical technique due to the precise and predictable results obtained.The definition of the objective of the study was first carried out using the PICO (Patient, Intervention, Comparison, Outcome) question method. Posteriorly, an updated literature review was carried out in the “PubMed” database using the keywords “Genioplasty and Virtual 3D Planning,” obtaining 11 articles for the study with the objective of defining the advantages and disadvantages of performing a virtually planned genioplasty, comparing it with the conventional technique.In the results, it is observed that virtually planned genioplasty presents greater precision, a reduction in surgical time, and a lower rate of complications than the conventional technique. Virtual planning using computer-aided design/computer-aided manufacturing technology presents good reproducibility in the patient with <2 mm variations between what was planned and what was obtained postoperatively, with statistically significant results (p < 0.001).In conclusion, virtually planned genioplasty with customized cutting guides and osteosynthesis plates achieves very precise surgery results with good reproducibility, reducing surgical time, intraoperative complications, and the difficulty of the surgical technique.
Keywords: genioplasty; virtual 3D planning; osteotomy; customized